The comparison of the efficacy of intra-peritoneal instillation along with local infiltration with bupivacaine versus placebo for post-operative analgesia after laparoscopic tubal ligation - Kakade, Aniket S.; Dudam, Naval; Panchanadikar, Tushar M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Intra-peritoneal instillation of local anesthetics has been shown to minimize post-operative pain after laparoscopic surgeries. The present study was undertaken with the following aim to compare the efficacy of intra-peritoneal instillation and local infiltration with bupivacaine versus placebo for post-operative analgesia after laparoscopic tubal ligation. To correlate the advantages and side effects of the drugs during the procedure. To establish a protocol for the use of bupivacaine instillation and infiltration for post-operative analgesia after laparoscopic tubal ligation. Methods: A prospective study was carried out in a tertiary care hospital attached to a teaching medical institute. Institutional ethics committee approval was obtained for this randomized control study (double blind) including 50 women who will be divided in two groups. Group A will be administered intra-peritoneal bupivacaine along with local infiltration. Group B will be administered normal saline. Post-operative pain will be monitored by a blind observer and rescue analgesia will be administered at visual analogue score of 3. Results: Both the groups were comparable with respect to age and BMI. The mean duration of analgesia in Group A with bupivacaine was 315.60±79.9 min (Median 300 min). The mean duration of analgesia in Group B with normal saline was 138.20±46.97 min (Median 150 min, p value <0.001). Conclusions: The study depicts a significant pain relief after use of bupivacaine. Bupivacaine instillation in the peritoneal cavity along with local infiltration of the drug gives prolongs pain relief as compared to normal saline.